Penerapan Rebusan Daun Seledri (Apium Graveolens L) Terhadap Tekanan Darah Pada Penderita Hipertensi Di Kelurahan Jalan Gedang RT 04 Kota Bengkulu - Frischa Putri Oktavia; Lia Fitriana; Ferna Dwi Mella; Fiyah Diniarti (Jurnal Dehasen Mengabdi, 2026)
Hypertension is one of the leading causes of premature death worldwide, accounting for 10.4 million deaths. The majority of hypertension sufferers worldwide are from developing countries. Pharmacologically, chemical drugs are widely used to treat hypertension. Furthermore, many researchers are now exploring plants that can be used as therapies, including those for hypertension. One non-pharmacological therapy for lowering blood pressure is complementary therapy. There are many types of complementary therapies, one of which is the use of celery leaves. Celery (Apium graveolens) has been proven effective in lowering high blood pressure because it contains potassium, a diuretic needed to help the body excrete water and sodium, thus lowering blood pressure. Based on these conditions, previous studies have proven the effect of celery leaf decoction on lowering blood pressure. This counseling aims to evaluate the effectiveness of celery leaf decoction (Apium graveolens) as a complementary therapy in lowering blood pressure in hypertensive patients with different risk characteristics. This study used a pre-post-test design with 20 residents, a case study, who underwent an intervention involving the consumption of 100 cc of celery leaf decoction twice daily for three consecutive days. The decoction was made from 40 grams of fresh celery leaves, boiled in 400 cc of water until 200 cc remained. Based on the results of this counseling, it can be concluded that celery leaf decoction has the potential to be an effective and easily applied complementary therapy in the management of hypertension, while also managing other risk factors such as lifestyle modification, dietary adjustments, and regular blood pressure monitoring to achieve optimal results.